Cucurbitacin B controls M2 macrophage polarization to suppresses metastasis via targeting JAK-2/STAT3 signalling pathway in colorectal cancer. (6th April 2022) - Zhang, Haoyue; Zhao, Bei; Wei, HuiZhen; Zeng, Hairong; Sheng, Dongya; Zhang, Yang
Abstract: Ethnopharmacological relevance: Cucurbitacin B (CuB), extracted from muskmelon pedicel, is a widely available triterpenoid molecule that exerts influence on various biological activities. Modern pharmacological studies have found that cucurbitacin B has many kinds of pharmacological anti-tumor and anti-metastasis functions. Aim of the study: To explore the mechanism of anti-tumor and anti-metastasis effect of cucurbitacin B. Materials and methods: The effect of cucurbitacin B on the growth of HCT116 and CT-26 was detected by CCK8; apoptosis was determined by flow cytometry and colony formation; the expression of apoptosis-related protein Bax, Bcl-2 and Cleaved-caspase-3 were examined by western Blot. To explore the underlying mechanism of cucurbitacin B against tumor, the Western blot, Immunofluorescence staining, Microscale Thermophoresis assays were used. Multiple molecular biology experiments were applied to validate the effect of polarization of cucurbitacin B-induced macrophages. The supernatant of Cucurbitacin B-induced macrophages and colon cells were co-cultured in vitro, and then transwell and wound healing assay were employed to the related phenotypes. C57BL/6 and BALB/c murine colon cancer model were also used to study the drug effects in vivo. Results: Cucurbitacin B distinctly induced the apoptosis of CRC cells. It was observed that cucurbitacin B not only inhibited the phosphorylation of JAK2 and STAT3, but also the translocation from the cytosol to the nucleus. Meanwhile, we observed that cucurbitacin B is bound to STAT3. Further experimentation demonstrated that cucurbitacin B reduced the polarization of M2 macrophage by down-regulating JAK2/STAT3 signaling pathway. Cucurbitacin B-induced M2-like macrophages were found to diminish the migration of CRC cells. In vitro study suggested that cucurbitacin inhibited the CRC cells proliferation via JAK2/STAT3 and suppressed the cell migration by suppressing M2-like macrophages polarization. Consistent with in vitro results, the cucurbitacin B therapy significantly inhibited tumor growth and metastasis in mice. Moreover, in vivo the treatment with cucurbitacin B enhanced anti-tumor immunity by regulating M2-like macrophages and promoted the expression of CD4 and CD8 in tumor microenvironment. Conclusion: Our results proved that cucurbitacin B might be a potential candidate agent for adjuvant therapy in the process of CRC growth and metastasis. Graphical abstract: Image 1